Establishing the institute of Hadith (Dar Al-Hadith) in Malaysia: a prelimenary study - Deraman, F.; Abd Rahman, A.A.; Amir, S.; Suliaman, I.; Ahmad, K.; Abdullah, M.; Ahmad Shah, F.; Moohd Yusoff, M.Y.Z.; Abd Razzak, M.M.; Mohd Noor, M.M.; Touhami Meftah, J.; Ariffin, S.; et al. (© IDOSI Publications, 2013, 2013)
The study and research on hadith forms rather a long history. It has entered into different phases of progress: from the earliest development into a phase of flourish, then another phase of stagnant period and later, a phase of regaining period of active progress of the field. This paper aims to discuss and examine the possibility to establish a formal government institution of Dar al-Hadis in Malaysia. There is a significant steps towards this project. The study of Hadith started with face to face deliverance of the hadith from Prophet Muhammad (p.b.u.h.) to his companions. The preservation of Hadith is one of the most important aspects in Islamic history. This paper implies that the preservation of hadith through institution establishment is vital especially in this modern age.